The SER Standards: a globally relevant and inclusive tool for improving restoration practice—a reply to Higgs et al - Gann, G.; McDonald, Tein; Aronson, J.; Dixon, Kingsley; Walder, B.; Hallett, J.; Decleer, K.; Falk, D.; Gonzales, E.; Murcia, C.; Nelson, C.; Unwin, A. (Blackwell Science Inc., 2018)
© 2018 Society for Ecological Restoration. In response to a critique by Higgs et al., this article clarifies the content and intent of the Society for Ecological Restoration's (SER) International Standards for the Practice of Ecological Restoration. Higgs et al. expressed concern that the SER Standards are not sufficiently underpinned by principles and risk disenfranchising some practitioners by narrowing what qualifies as ecological restoration. To demonstrate that these concerns are unfounded, we discuss the policy context and principles on which the Standards are based, its organizational structure, the innovative and inclusive approach used for development, and highlight significant errata by Higgs et al.